Disease Activity (Rheumatoid Arthritis Disease Activity Index-5) in Patients With Rheumatoid Arthritis and its Association With Quality of Life, Pain, Fatigue, and Functional and Psychological Status - İsmihan SUNAR,; Yeşim GARİP,; Özlem YILMAZ,; Hatice BODUR,; Şebnem ATAMAN, (Archives of Rheumatology, 2015)
Objectives: This study aims to determine disease activity in patients with rheumatoid arthritis by Rheumatoid Arthritis Disease Activity Index-5 (RADAI-5), and to evaluate its association with the quality of life, pain, fatigue, and functional and psychological status. Patients and methods: A total of 170 rheumatoid arthritis patients (30 males, 140 females; mean age 55.2±11.3 years; range 28 to 82 years) were included in the study. Quality of life was evaluated by using Rheumatoid Arthritis Quality of Life Scale. Stanford Health Assessment Questionnaire was used for evaluating functional status, and Beck Depression Scale for psychological status. Level of fatigue was assessed by Fatigue Severity Scale. Disease activity was measured by using Disease Activity Score-28 (DAS28) and RADAI-5. Results: Mean RADAI-5 score was 3.9±2.7, and mean DAS28 score was 3.3±1.4 (moderate disease activity). According to RADAI-5, 16.5% of the patients were in remission, 28% had mild disease activity, 27% had moderate disease activity, and 29% had high disease activity. RADAI-5 was strongly correlated with visual analog scale-pain, DAS28, Beck Depression Scale, Fatigue Severity Scale, Rheumatoid Arthritis Quality of Life Scale, and Health Assessment Questionnaire (r= 0.91, 0.81, 0.78, 0.75, 0.75 and 0.72, respectively) (p<0.0001). Disease activity values measured with RADAI- 5 were compatible with the ones measured with DAS28. Conclusion: RADAI-5 is a short, practical questionnaire that can easily be administered by the patient in a busy clinical practice setting. It can be used as a rheumatoid arthritis outcome measure to estimate the impact of the disease and evaluate health outcome in clinical studies.